2008
DOI: 10.1121/1.2839140
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the acoustic radiation force in microfluidic chambers

Abstract: A procedure is demonstrated to quantitatively evaluate the acoustic radiation forces in microfluidic particle manipulation chambers. Typical estimates of the acoustic pressure and the acoustic radiation force are based on an analytical solution for a simple one-dimensional standing wave pattern. The complexities of a typical microfluidic channel limit the usefulness of this approach. By leveraging finite elements, and a generalized equation for the acoustic radiation force, channel designs can be investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…3). Fisher's combined P analyses (Fisher and Miles 2008), which combined the P values from association tests in the study populations, showed that rs10816533 has more strong association signal ( P = 1.55 × 10 −6 ).…”
Section: Replication Studymentioning
confidence: 99%
“…3). Fisher's combined P analyses (Fisher and Miles 2008), which combined the P values from association tests in the study populations, showed that rs10816533 has more strong association signal ( P = 1.55 × 10 −6 ).…”
Section: Replication Studymentioning
confidence: 99%
“…Due to AF of CNP11164 (AF = 0.0031) and CNP10799 (AF = 0.003) is smaller than 1%, only CNP182 and CNP267 were analyzed for replicate association and reached p values at 2.39E-01 and 5.66E-03, respectively (Table 2). Meta-analysis (Fisher's combined p method [25]) was used to combine association tests in the two populations. The Fisher's combined p value (p = 3.09E-04) for CNP267 is nearly approaching the significant level after multiple testing (0.05/194 = 2.58E-04).…”
Section: Resultsmentioning
confidence: 99%
“…To correct for the effect of potential population stratification, we conducted a principal component analysis on genome-wide SNP data with EIGENSTRAT [29] and included the top ten principal components as covariates. Fisher’s method [30] was used to combine the p -values from the discovery sample and replication sample.…”
Section: Methodsmentioning
confidence: 99%